Molecular Characterization and Sequencing of a Gene Encoding Mannose Binding Protein in an Iranian Isolate of Acanthamoeba castellanii as a Major Agent of Acanthamoeba keratitis - M Niyyati; S Rezaie; F Rahimi; M Mohebali; AH Maghsood; SH Farnia; M Rezaeian (Tehran University of Medical Sciences, 2008)
Background: Acanthamoeba castellanii is the important cause of amoebic keratitis in Iran. The key molecule in pathogenesis of Acanthamoeba keratitis is Mannose Binding Protein (MBP) led to adhesion of amoeba to corneal epithelium. Subsequent to adhesion other cytopathic effects occur. The goal of this study was to identify the molecular characterization of a gene encoding MBP in an Iranian isolate of A.castellanii in order to pave the way for further investigations such as new therapeutic advances or immunization. Methods: A.castellanii was cultured on non nutrient agar. Extraction of DNA was performed by phenol-chloroform method. After designing a pair of primer for the gene encoding MBP, PCR analysis was performed. Finally, the PCR product has been sequenced and the result submitted to the gene data banks. Results: An MBP gene of 1081 nucleotides was sequenced. This fragment contained three introns and encodes a protein with 194 amino acids. Homology search by Blast program showed a significant homology with the MBP gene in gene data banks (96%). Besides, the identity of amino acids with the other MBPs in gene data banks was about 86%. Conclusion: We isolated and sequenced a gene fragment encoding MBP in an Iranian isolate of A.castellanii. Molecular characterization of this important gene is the first step in pursuing researches such as developing better therapeutic agents, immunization of population at risk or even developing a diagnostic tool by PCR techniques.